Antibacterial Activity and Bioautography Test of Ethanol Extract of Kitolod (Isotoma longiflora (L.) C. Presl.) Leaves against Staphylococcus aureus and Salmonella typhi using Ultrasound-Assisted Extraction - Fajrin Ahidannisa Yuhdi; Ika Trisharyanti Dian Kusumowati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Isotoma longiflora (L.) C. Presl. (Kitolod) is recognized for its potential as a natural antibacterial agent, with prior studies on its leaf extracts demonstrating inhibitory effects against Staphylococcus aureus and Salmonella typhi. This research aimed to investigate the antibacterial efficacy of I. longiflora leaf ethanol extracts, determine their phytochemical composition, and identify the active compounds responsible for the observed antibacterial activity. Extracts were prepared using ultrasonic-assisted extraction (34°C, 38 Hz, 40 minutes) with 70%, 85%, and 96% ethanol solvents. Antibacterial activity was assessed using the well diffusion method at concentrations of 40%, 60%, and 80%, against positive controls (ampicillin 10 µg and chloramphenicol 30 µg) and a negative control (100% DMSO). The highest activity against S. aureus was demonstrated by the 96% ethanol extract at 80% concentration, yielding an average inhibition zone of 13.3 ± 1.2 mm against S. typhi. The 85% ethanol extract at a concentration of 80% was most effective, with an inhibition zone of 9.5 ± 0.7 mm. Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, and phenolics in both the 85% and 96% ethanol extracts. However, the attempt to identify the specific active antibacterial compounds via the contact bioautography method yielded negative results, suggesting the need for further isolation and identification studies.